Working-class minority students' routes to higher education - Espinoza, Roberta (New York : Routledge, 2012)
"While stories of working-class and minority students overcoming obstacles to attend and graduate from college tend to emphasize the individualistic and meritocratic aspect, this book - based in extensive empirical study of American high school classrooms, and in theories of social and cultural capital - examines the social relations that often underpin such successes, highlighting the significant formal and informal academic interventions by educators and other education professionals"--
Includes bibliographical references (pages [135]-143) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Minorities -- Education (Higher) -- United States; Working class -- Education (Higher) -- United States; Universities and colleges -- United States -- Admission; Educational equalization -- United States; Electronic books